Improved Understanding of Electricity Concept and Creativity of Students with PjBL-C Learning Model (Project Based Learning Community) - Bambang Surahmadi (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2018)
This study aims to improve understanding of electricity concept and creativity of learners through the model of learning PjBL-C. Project-based learning is a learning model involving learners in problem-solving and other meaningful task assignments, resulting in a project or product in understanding learning. PjBL-C is a collaborative PjBL and community where learners learn directly on BTL. Subjects in this study were students of class IX-A SMP Negeri 1 Temanggung, amounting to 30 students. This form of research is a classroom action research as much as two cycles. Each cycle consists of 4 stages: planning, action implementation, observation, and reflection. Data analysis technique used is descriptive analysis model. Data collection methods used were observation and test. The result of his research shows that the learning model of PjBL-C can improve the students' understanding of the concept of IX-A students of SMP Negeri 1 Temanggung. This is evidenced by the percentage of learning completeness of students that before the action is given to cycle 1 is increased 16%, increase from cycle I to cycle II by 44%, and increase from beginning to cycle II by 60%. PjBL-C learning model can also improve the creativity of students of class IX-A SMP Negeri 1 Temanggung. This is evidenced by the percentage of the average value of learners is the increase from cycle I to cycle II by 30%. The conclusion of this research is through the use of model PjBL-C can improve understanding of electric concept and creativity of learners